Pengaruh Kombinasi Surfaktan Natrium Lauryl Sulfat dan Benzalkonium Klorida Terhadap Kelarutan Ibuprofen - Syofyan, Syofyan; Safari, Tuti Agustia; Azhar, Rieke (Fakultas Farmasi Universitas Andalas, 2013)
A study on the influence of sodium lauryl sulfate and benzalkonium chloride combination on the solubility of ibuprofen has been done. The solubility of ibuprofen with sodium lauryl sulfate, benzalkonium chloride and itâs combination was determined by surface tension method with Du Nouy Tensiometer and by refractive index method with Refractometer ABBE. The solubility was determined at surfactant concentration above the CMC value. Results showed that formula 4 gave the highest solubility of ibuprofen (96,25 %). Combination of the surfactants caused precipitation.